Calea × crassa (Neurolaeneae: Asteraceae), a new nothospecies from Paraná state, Brazil - Bueno, Vinicius R.; Cassol, Ana P. V.; Leroy, Carolina J.; Bueno, Marcelo L.; Heiden, Gustavo (Phytotaxa, 2023)
Calea × crassa, a new nothospecies is described and illustrated. The thickened pale olivaceous leaf margins along with the mucronate teeth are unique morphological features shared with its parental species C. ilienii and C. monocephala. The nothospecies can be distinguished from C. ilienii by the concolorous leaves (vs. discolorous leaves), involucre 6-seriate (vs. 5-seriate), second series of phyllaries with foliaceous base (vs. scarious base), and bigger scales 1.8–1.9 mm long, when present (vs. 1–1.5 mm, when present). It is differentiated from C. monocephala by the third series of phyllaries with acuminate apex (vs. apiculate, sometimes rounded), the narrow oblong sixth series of phyllaries (vs. oblanceolate, when present), and the bigger scales 1.8–1.9 mm long, when present (vs. 2.1–2.2 mm, when present). In addition to these characters, a principal component analysis also supports the traits differentiating the new hybrid from its parental taxa. Geographic distributions of C. × crassa and its parental species are mapped, including a modelled prediction occurrence map for the nothospecies. A taxonomic key for identification of the parents and the nothospecies is provided and the key morphological characters of these three taxa are illustrated.